1984
DOI: 10.1159/000183260
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalemia and Prostaglandin Overproduction in Bartter’s Syndrome

Abstract: In 2 adult patients with Bartter’s syndrome, in whom chloride reabsorption at the diluting segment of the nephron was markedly reduced, serum potassium concentration could be improved with oral administration of a large amount of potassium chloride. In both cases, improvement of seerum potassium levels with oral potassium load resulted in an increase in plasma renin activity (PRA) and plasma aldosterone concentration (PAC), a decrease in urinary excretion of prostagladin E2 (PGE2) and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It has long been observed that epithelial transport function and urinary concentrating ability in the mTAL were compromised severely during hypokalemia (Rutecki et al 1982; Senba et al 1984; Unwin et al 1994). Our present finding that the sensitivity of the apical K channel to the extracellular Ca 2 + concentration is significantly enhanced in the mTAL from rats on a KD diet may be useful to explain why some pathophysiological observations occurred during hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…It has long been observed that epithelial transport function and urinary concentrating ability in the mTAL were compromised severely during hypokalemia (Rutecki et al 1982; Senba et al 1984; Unwin et al 1994). Our present finding that the sensitivity of the apical K channel to the extracellular Ca 2 + concentration is significantly enhanced in the mTAL from rats on a KD diet may be useful to explain why some pathophysiological observations occurred during hypokalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fact that high concentrations of PGE 2 inhibit the apical K ϩ channels by a PKC-dependent mechanism may also be important to understand the beneficial effect of inhibiting prostaglandin synthesis in treatment of Bartter's syndrome. One of the characteristics of Bartter's syndrome is an increase in plasma PGE 2 level (29). Inhibition of cyclooxygenase (COX) improves the manifestation of the disease (27).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that excessive biosynthesis of prostaglandins is the central defect in Bartter syndrome has been especially attractive given the spectacular improvement that usually follows treatment with cyclooxygenase inhibitors. However, it is now evident that the altered eicosanoid metabolism is only an epiphenomenon of chronic hypokalemia and angiotensin excess [72,73].…”
Section: Pathophysiologymentioning
confidence: 99%